Medical instrumentation application and design - Webster, John G. (Houghton Mifflin Company, 1992)
The book provides both in text worked examples and homework problems at the end of each chapter. Problems are designed to cover a wide variety of applications ranging from analysis of the waves of the electrocardiogram to circuit design of biopotential amplifiers and identification of electric safety hazards.